1HMRS results of hippocampus in the patients with obsessive-compulsive disorder before and aft er cognitive behavioral therapy - Atmaca, Murad; Yildirim, Hanefi; Yilmaz, Seda; Caglar, Neslihan; Mermi, Osman; Gurok, M. Gurkan; Turkcapar, Hakan (Taylor & Francis Ltd, 2015)
Objective. In the present study, we examined the effects of cognitive behavioral therapy (CBT) on the hippocampal neurochemistry in patients with obsessive-compulsive disorder (OCD). Methods. Twelve patients with OCD and same number of healthy controls were included into the study. Neurochemical variables of the hippocampus were measured before and after the CBT treatment in the patient group. Results. At baseline, the patients with OCD had significantly lower ratio of N-acetyl-l-aspartate/choline (NAA/CHO) compared with that of healthy control subjects. When comparing pre-treatment results of the patient group with those of post-treatment ones using paired t-test, we found that NAA/CHO ratio increased from 2.47 +/- 0.64 to 3.66 +/- 0.88, with a statisical significance. Conclusions. The findings may implicate that CBT increases the level of NAA which is a marker of neuronal integrity.
Keywords: OCD; CBT; MRS; hippocampus